CARE AND EDUCATION OF BABIES AND TRAINING OF LEADERS - Mello, Suely Amaral [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2017)
What do we want from our toddlers? Are we aware that the way we relate to them teaches them a way of being with others and forms the basis upon which they begin to form their personality? Do we know that the way we care for and educate children in the first year of life and their experience start to constitute their intelligence? In this paper, I want to discuss the contributions of historical-cultural theory to the care and education of toddlers and, accordingly to this theory, present the practices of the Pikler-Loczy approach to care and education at this age. By doing this, I want to contribute to substantiate that theory, showing that theories do became practices. To do this, it is necessary to have practices that concretize the guidelines that we learn from the theoretical approach we adopt, according to our conceptions of human development, education, child, childhood and of how children learn.
Keywords: Cultural historical theory; toddlers; care and education